Venous thromboembolism risk factors in pediatric patients with high-grade glioma: a multicenter retrospective study - Yanxia Chen; Wenjing Fei; Yaqin Shi; Weiwei Ma; Wei Jiao; Fengqin Tao; Jie Zhu; Yuhai Wang; Xiaoyan Feng (Frontiers in Pediatrics)
BackgroundVenous Thromboembolism (VTE) is a significant complication in pediatric high-grade glioma (pHGG) patients, impacting prognosis and treatment outcomes. Identifying unique risk factors and pathophysiology in children is essential for targeted prevention and treatment.MethodsA multicenter retrospective analysis was conducted on pHGG patients enrolled between January 2012 and January 2024 at two hospitals. Data were collected from electronic medical records and follow-ups, focusing on VTE occurrence, clinical characteristics, and treatment outcomes. Statistical analyses included t-tests, Mann–Whitney U-tests, chi-square tests, and Cox regression models to identify risk factors and their impact on survival.ResultsOut of 216 screened patients, 168 met the inclusion criteria. The mean age was 9.87 ± 3.67 years, with 37.5% experiencing VTE. Tumor volume, grade, and specific genetic mutations significantly influenced VTE occurrence. Anticoagulation therapy, Isocitrate Dehydrogenase 1 (IDH1) mutations, O6-Methylguanine-DNA Methyltransferase (MGMT) methylation, radiotherapy, chemotherapy, and prolonged bed rest were protective against VTE, while increased tumor volume, Grade 4 glioma, Epidermal Growth Factor Receptor (EGFR) positivity, p53 mutations, glucocorticoid therapy and central venous catheter placement (CVCP) placement promoted VTE risk. The median survival time was 51.4 months, and VTE occurrence negatively impacted patient prognosis.ConclusionThis study highlights the risk factors for VTE in pHGG patients, emphasizing the need for tailored prevention and treatment strategies. The findings underscore the importance of clinical characteristics, genetic profiles, and treatment modalities in managing VTE and improving survival outcomes in pHGG.